Analysis of the Relationship between Brand Loyalty and Market Share: A Comparative Study of Durable and Non - Durable Products in India - Agarwal, P. K.; Kumar, Pradeep; Gupta, Swati (Indian Journal of Marketing, 2012)
A Brand is any name, symbol, term, design or blend of any of them for the purpose of recognizing or identifying any goods or services of a service or product provider or a group of them, which can also help them in differentiating from all other brands which compete with them. Therefore, in short, a brand helps to recognize the manufacturer or it can be a seller. Till now, if you thought a brand to be only the name of a product or service, then surely you are missing an important concept. Vital challenges posed in front of branding is to improve the deep set of meanings for a brand. Well, the distinguishing factor of any marketer is to form, protect or augment a brand. The level of success of any brand lies in making a identifiable (it could be a consumer, as well as an industrial brand); it could be a person, a place, a product, or services. Branding is amplified in a way that the customer who buys this product or a consumer who will use this product would be satisfied by the product. If the product succeeds in providing utility over many years, then it extracts the advantage of familiarity and reliability. The added utility comes from the experience which the consumer has formed by using the product; and in the process, reliability, character formation, familiarity and risk reduction are also formed. (Bradley 1995; Leslie de Chernatony, McDonald, 1992; Doyle, Jones,1986).